Time to surgery for open hand injuries and the risk of surgical site infection: a prospective multicentre cohort study. (July 2020) - Davies, James; Roberts, Tobias; Limb, Richard; Mather, David; Thornton, Daniel; Wade, Ryckie G.
Whether delaying surgery increases the risk of infection in open hand injuries is an important but unresolved topic. This prospective cohort study included 983 consecutive adults with open hand injuries treated surgically over 1 year. The risk ratio (RR) for surgical site infection was estimated by logistic regression. The median time from injury to surgery was 20 hours (range 4–90). Forty-one patients (4%) developed an infection. The risk of infection was not affected by the time to surgery (adjusted risk ratio 1.0 [95% CI: 1.0 to 1.0]) or preoperative antibiotics (adjusted risk ratio 1.8 [95% CI: 0.2 to 13]), which were provided to 95% of patients. Skin loss increased the risk of infection (adjusted risk ratio 2.6 [95% CI: 1.3 to 5.0]). Delaying surgery for open hand injuries by 4 days does not appear to increase the risk of surgical site infection. Level of evidence: II